Biomechanical upper-extremity performance tests and isokinetic shoulder strength in collision and contact athletes. Issue 16 (18th August 2021) - Fanning, Edel; Daniels, Katherine; Cools, Ann; Miles, Josh J.; Falvey, Éanna
ABSTRACT: The aim of this study was threefold (1) to assess the reliability of three upper-extremity performance tests: a countermovement push up, press jump and drop box land, performed on a set of dual-force plates (2) to examine whether there was an association between isokinetic dynamometry and the performance tests in a non-injured cohort of collision/contact athletes and (3) to establish a normal descriptive profile of the vertical ground reaction forces from the performance tests, in a cohort of contact/collision athletes. The study was split into two sub-sections; the inter-day reliability of three upper-extremity performance tests (n = 21) and a descriptive, correlation study investigating the relationship between isokinetic dynamometry and performance tests metrics (n = 39). We used intraclass correlation coefficients (absolute agreement, 2-way mixed-effects model) with 95% confidence intervals to quantify inter-day reliability of all variables. We used Pearson correlation coefficients to investigate associations between isokinetic strength and vertical ground reaction force asymmetry variables. Inter-day reliability was moderate-to-excellent for the upper-extremity performance tests (ICC 0.67–0.97). There was no statistically significant correlation between external and internal rotational peak torque and the variables of CPMU, PJ and BDL (r range = .02–.24).These upper-extremity tests are reliable for use with male contact/collision athletes.